Effect feed additives on performance of beef cattle finished in feedlot - Guerreiro, Pedro (2019)
The objective of this study was to evaluate the effects of three feed additives - sodium monensin (MON; 31.3 mg/kg DM), monensin plus the buffer additive Lithothamnium calcareum (MON+LC; 31.3 mg/kg DM + 5g/kg DM) or a blend of essential oils (BEO; 0.3 g/kg DM) and its interactions with two racial groups of beef cattle - Nellore (NEL) vs. Crossbreds (CROSS) - on a finishing feedlot diet. Ninety Nellore bulls (initial BW = 394 ± 34 kg) and ninety crossbreds (initial BW = 406 ± 31 kg), were fed for 112 days a basal diet containing 8.5% sugarcane bagasse, 42.2% of fine ground corn, 41.7% of citrus pulp, 5% of soybean meal, 1.3% of urea, 0.35% of sodium chloride and 0.95% of minerals and vitamins (DM basis), varying only the type of additive added to the diet. Treatments were NEL+MON; NEL+MON+LC; NEL+BEO; CROSS+MON; CROSS+MON+LC; CROSS+BEO. The statistical design was a randomized complete block with a 2 x 3 factorial arrangement (2 racial groups and 3 feed additives). It were evaluated: dry matter intake (DMI), average daily gain (ADG), feed efficiency (G:F), hot carcass weight (HCW), carcass dressing and observed NE of the diets during the experimental period. The data were analyzed using the PROC MIXED of SAS. Pen was considered the experimental unit. There were no interactions between racial groups and feed additives (P > 0.05). Crossbred bulls presented higher DMI (P < 0.001), ADG (P < 0.001) and final BW (P < 0.001) and HCW (P < 0.001) than Nellore bulls. Crossbreds were also more efficient in energy utilization for maintenance and gain than NEL (P < 0.001). Dry matter intake was lower (P <= 0.030) for animals fed MON+LC (8.126 kg) than animals fed BEO (9.255 kg). Average daily gain (P = 0.177) and final body weight (P = 0.238) were not affected by treatments. Feed additives did not alter hot carcass weight (P = 0.252) and dressing (P = 0.826). However, feed efficiency was greater (P <= 0.05) for animals fed MON (0.151) than for animals fed BEO (0.138). Net energies of maintenance and gain were higher (P <= 0.05) for animals fed MON (2.182 and 1.490 Mcal/kg) than for animals fed BEO (2.020 and 1.362 Mcal/kg). Ratio of observed:expected NE concentrations were also influenced by feed additives (P <= 0.05). Animals fed MON presented observed net energies values 32.3% and 43.2% higher than expected for maintenance and gain, respectively, whereas animals fed BEO presented observed net energies 22.4% and 30.9% higher for maintenance and gain, respectively. The combination of the seaweed buffer with monensin had no positive nor synergistic effects when compared to monensin alone. Monensin was more efficient than the commercial BEO in feed efficiency and nutrient utilization.